2019
DOI: 10.1016/j.visres.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ center bias in free viewing of real-world scenes

Abstract: While distributional learning has been successfully demonstrated for auditory categorization, this study tests whether this mechanism also applies to object categorization: Tenmonth-olds (n = 38) were familiarized with either a unimodal or bimodal distribution of a visual continuum. Using automatic eye tracking, we assessed categorization through the alternating/nonalternating paradigm. For infants in the bimodal condition, their average dwell time was larger for alternating trials than for nonalternating tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 82 publications
2
34
1
Order By: Relevance
“…However, more work should be done to determine how these preferences interact with experimental design in order to potentially obscure the capabilities of infants, in particular because central bias is often established in scene viewing paradigms (e.g. van Renswoude et al, ) but has not been as carefully examined in visual paired comparison tasks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, more work should be done to determine how these preferences interact with experimental design in order to potentially obscure the capabilities of infants, in particular because central bias is often established in scene viewing paradigms (e.g. van Renswoude et al, ) but has not been as carefully examined in visual paired comparison tasks.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have been demonstrated in infants as well. For example, van Renswoude, Berg, Raijmakers, and Visser (2019) found that infants focused strongly on centrally located aspects of complex scenes as compared to peripheral aspects. A noteworthy caveat is that the infants showed a weaker central bias when the most salient information in the scene was located to the periphery (van Renswoude et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are important in modeling adult eye movements (Foulsham & Kingstone, ), and they predict fixation locations above chance level (Tatler & Vincent, ). Recently, it was shown that infants also demonstrate the horizontal bias (van Renswoude, Johnson, Raijmakers, & Visser, ) and the central bias (van Renswoude et al, ). This indicates that infants, similar to adults, are more likely to fixate central locations and locations along the horizon.…”
Section: Introductionmentioning
confidence: 99%